Yeast-derived glycolipids disrupt Candida biofilm and inhibit expression of genes in cell adhesion - Kwanrutai Watchaputi; Pattanan Songdech; Channa Jayasekara; Panupong Puttarak; Erwin Lamping; Richard D. Cannon; Nitnipa Soontorngun (Scientific Reports)
Abstract Candida albicans is a leading fungal pathogen in humans, responsible for infections that span from mucosal surfaces to severe systemic diseases. This study aimed to investigate potential ability of yeast-derived glycolipids from Meyerozyma guilliermondii as an antifungal against Candida albicans biofilms. Glycolipid extract (64 µg/mL) reduced metabolic activity by 50% in both immature and mature biofilms, while biofilm mass was reduced at higher concentrations of 128 and 256 µg/mL, respectively. Adhesion, a key step in biofilm formation, decreased by over 50% when cells were treated with glycolipids (16 µg/mL). Gene expression analysis indicated that glycolipids downregulated key adhesion-related gene ACE2, confirming their role in disrupting C. albicans adhesion. Importantly, structural changes in C. albicans biofilms, including reduced hyphal production and wrinkled cell surfaces, were observed under SEM. Nocodazole, a cell cycle synchronizer, arrested cells in the G2/M phase, enhancing glycolipid’s effects on lowing expression of biofilm-related genes. Lipidomics analysis also revealed a compound with same mass as sophorolipid. Furthermore, purification glycolipid fraction revealed two main forms: lactonic and acidic, compared to standards. Acidic fraction showed superior antibiofilm and anti-inflammatory activity with low toxicity. These findings highlight the potential of yeast-derived glycolipids for biopharmaceutical applications, particularly in treating Candida biofilms.